Ideology and Attitudes toward Jews in U.S. Public Opinion: A Reconsideration - Cohen, Jeffrey E. (Religions, 2024)
Antisemitism has been found on both the extreme left and right among political elites. However, at the mass public level, limited research suggests right-wing antisemitism, but not much left-wing antisemitism. This paper challenges that research, at least for the U.S., offering an alternative theory. The theory argues that the lowest levels of antisemitism will be found among mainstream liberals and conservatives. Ideological moderates will exhibit higher rates of antisemitism, while those lacking an ideological orientation will show still higher antisemitic rates. Extremists of the right and left may be more antisemitic than mainstream conservatives and liberals, but the inability of standard ideological self-placement questions to distinguish extreme ideologues from the very conservative/liberal makes it difficult to test the extremism hypothesis. Numerous items measuring attitudes towards Jews in the U.S. across five major surveys finds overwhelming support for the mainstream philosemitism theory. The conclusion puts the findings into perspective and offers suggestions regarding future research.